THE USE OF LIPOPOLYSACCHARID AND GLUCAN AS IMMUNMODULATOR OF WOUND INFECTIONS - Melconian, Alice; Mahmood, Suhad (Iraqi Journal of Science, 2024)
One hundred clinical samples were collected from infected wounds of patients admitted in Al-Yarmouk and Al-Kadymia hospital from 1-3 to1-9-2004.The results of aerobic culture appeard that 86% of bacterial isolates showed positive results and the bacteria Pseudomonasaeruginosa and klebsiella pneumonia was the most common isolates.Antibiotic susceptibility test was performed for P.aeruginosa and K.pneumonia and the results appear the two types of bacteria sensitive to imipenium and resistant to amoxiclave and cephalexin.Lps was extracted from the most drug resistant isolate P.aeruginosaa(Pa8) by hot phenol method and partial purified by gel filtration chromatography using sepharos-6-B and the results showed that carbohydrate and protein ratio in partial purified extracted were 37.5%and1.5% respectively,and the extract was free of amino acid